Factors associated with early resumption of sexual intercourse among women during extended postpartum period in Northwest Ethiopia: a cross sectional study - Birye Dessalegn Mekonnen (BMC, 2020)
Abstract Background Postpartum sexual health and practice need to be integrated in the current maternal healthcare services to address sexual health problems. However, postpartum sexual practice has received little attention, and was not often discussed by healthcare providers during prenatal and postnatal care. Thus, this study was aimed to assess early resumption of sexual intercourse and associated factors among postpartum women in Gondar city, Northwest Ethiopia. Methods A community based cross-sectional study was conducted from January 20 to February 20, 2020. A systematic random sampling technique was used to select 634 postpartum women. A pretested, structured and interviewer-administered questionnaire was used to collect data. Data were entered into Epi Info 7.2.2 and exported to SPSS version 20 for analysis. Bivariable and multivariable logistic regressions analysis were done. Variables with p- value of < 0.05 were considered as statistically significant. Results The magnitude of early resumption of sexual intercourse after childbirth was found to be 26.9% (95% CI: 23.2, 30.8). Urban resident (AOR = 6.12, 95% CI: 2.41, 15.66), parity of one (AOR = 2.26, 95% CI: 1.66, 7.78), husband demand (AOR = 2.66, 95% CI: 1.72, 4.11), postnatal care (AOR = 1.45, 95% CI: 1.06, 2.18) and use of family planning (AOR = 2.72, 95% CI: 1.51, 3.43) were factors significantly associated with early resumption of sexual intercourse. Conclusion The study found that more than one fourth of women had resumed sexual intercourse within six weeks of following childbirth. The finding of this study suggests the need of integrating discussions of postpartum sexual activity into routine prenatal, intrapartum and postnatal care with collaborative effort of policy makers, program planners, health care providers and other stakeholders. Moreover, spousal communication on postpartum sexual activity should be encouraged.